Engineering Characteristics of Curcuma Flour (Curcuma xanthorrhiza Roxb.) from Convection Drying - Abadiyah, Najati; Lestari, Ning Puji; Taruna, Iwan; Purbasari, Dian; Sutarsi, Sutarsi (The University of Lampung, 2024)
Curcuma is a herbs having a lot of advantages for human health. The fresh rhizome has a lot of disadvantages especially from the volume and low quality. To maintain the quality, curcuma should be processed to curcuma flour. This study was carried out to determine the engineering properties including water content, color, bulk density, water absorption, oil absorption, and angle of repose of curcuma flour ground after convection drying. The research method used in this study was CRD (completely randomized design) with 2 factors, namely drying temperature (40 °C, 50 °C, and 60 °C) and flouring or milling duration (6, 8, and 10 min). Curcuma rhizome was pre-treated with a convection drying. After milling process, the flour was sieved to have particle size of 60 mesh. Statistical analysis included ANOVA (Analysis of Variance), Duncan post-hoc test, and correlation test. The result revealed the curcuma flour has engineering properties including bulk density (0.35 – 0.38 g/ml), water content (7.97% – 11.77%), water absorption (2.78 – 3.79 ml/g), angle of repose (27.99° – 30.44°), color brightness L (67.07 – 71.78), red-green chrome a (7.67 – 8.92), yellow-blue chrome b (51.37 – 55.13), and total color change ∆E (57.42 – 62.12). Keywords: Convection dryer, Curcuma, Drying, Engineering characteristics, Flour.